The Spatio-Temporal Evolution of Overlying Rock Structure and Mine Pressure Behavior in a Short-Distance Coal Seam Face. (27th October 2022) - Zhou, Yupu; Cui, Feng; Jia, Chong; Feng, Ganggui; Gao, Yuanjiang; Dong, Shuai
Abstract : This research is aimed at exploring the evolution of overlying strata structure and the ground pressure in the working face mining of close-distance coal seams. By taking the Xiashijie Coal Mine as an example, the direct relationship between the rotation angle of key blocks of overlying strata and the subsidence of key blocks and the length of rock blocks was deduced using theoretical analysis and similar simulation experiments, and the critical criterion of basic overlying strata breaking was formed. Through the real-time monitoring of the characteristics of overlying strata and its pressure, the evolution of overlying strata structure and the ground pressure in the working face mining of close-distance coal seams could be clarified. The results show that the main factors that affect the turning angle of key blocks are the subsidence of key blocks and the length of rock blocks. When the subsidence and turning angle of rock blocks are larger and the length is smaller, the rock blocks are prone to rotational deformation and instability. The lower coal mining of the nearby coal seam group is more difficult due to the overlying strata caving in upper coal mining, and the damage height is about 335 mm higher than that in the upper coal. When mining over the same distance between the upper and lower coal seams of the close-distance coal seam group, fewer weightings are generated when mining the lower coal seam working face, the average weighting step is longer, and the average single weighting value is high. The research results provide a basis for the safe mining of close coal seams.